Sotos Syndrome, Isolated Left Ventricular Non Compaction Cardiomyopathy and Ventricular Pre Excitation: A Case Report. - Sassara Marco; Ruggiero Massimo; Tota Francesco; Musc Sergio; Bulzis Gabriella; Rutigliano David; Frasso Giulia; Carbone Mariangela; Tesorio Maria; Scicchitano Pietro; Caldarola Pasquale; Matteo Ciccone Marco (Journal of Hypertension and Cardiology, 2013)
We report the case of a 22 year-old-male patient affected by Sotos syndrome was preoperatively and urgently evaluated for tracheal stent implantation due to respiratory insufficiency caused by idiopathic tracheal stenosis. Rest electrocardiogram detected a ventricular pre excitation; a transthoracic echocardiography showed a classic pattern fulfilling criteria for isolated left ventricular non compaction. At the best of our knowledge this is the first report of a patient suffering from Sotos syndrome and simultaneously affected by isolated left ventricular non compaction and ventricular pre excitation.
Keywords: Sotos Syndrome